Conversations with the Conroys : interviews with Pat Conroy and his family - Edgar, Walter B., 1943-; Finney, Nikky (University of South Carolina Press : Published in Cooperation with South Carolina Educational Television and the Humanities Council, 2015)
"A New York Times best-selling author of eleven novels and memoirs, Pat Conroy is one of America's most beloved storytellers and a writer as synonymous with the South Carolina lowcountry as pluff mud or the Palmetto tree. As Conroy's writings have been rooted in autobiography more often than not, his readers have come to know and appreciate much about the once-secret dark familial history that has shaped Conroy's life and work. Conversations with the Conroys opens further the discussion of the Conroy family through five revealing interviews conducted in 2014 with Pat Conroy and four of his six siblings: brothers Mike, Jim, and Tim and sister Kathy. In confessional and often comic dialogs, the Conroys openly discuss the perils of being raised by their larger-than-life parents, USMC fighter pilot Col. Don Conroy (the Great Santini) and southern belle Peggy Conroy (née Peek); the complexities of having their history of abuse made public by Pat's books; the tragic death of their youngest brother, Tom; the chasm between them and their sister Carol Ann; and the healing, redemptive embrace they have come to find over time in one another. With good humor and often-striking candor, these interviews capture the Conroys as authentic and indeed proud South Carolinians, not always at ease with their place in literary lore, but nonetheless deeply supportive of Pat in his life and writing. Edited and introduced by the Palmetto State's preeminent historian, Walter Edgar, Conversations with the Conroys includes the first publications of Pat Conroy's interview with Edgar as the keynote address of the 2014 One Book, One Columbia citywide "big read" program, the unprecedented interview with the Conroy siblings for SCETV Radio's Walter Edgar's Journal, the resulting live Conroy Family Roundtable held at the 2014 South Carolina Book Festival, and a recent interview in Charleston following Pat Conroy's induction into the Citadel's Athletics Hall of Fame. This collection is augmented with an afterword from National Book Award-winning poet Nikky Finney and nearly fifty photographs, many from the Pat Conroy Archive in the Irvin Department of Rare Books and Special Collections, University of South Carolina Libraries, and published here for the first time. Through the resulting treasure trove of text and images, this volume is as much a keepsake for Conroy's legion of devoted fans as it is a wealth of insider information to broaden the understanding of readers and researchers alike of the idiosyncratic world of Pat Conroy and his family"--